Heat and mass transfer investigation of a chemically reactive Burgers nanofluid with an induced magnetic field over an exponentially stretching surface. (December 2021) - Khan, Muhammad N; Nadeem, Sohail; Abbas, Nadeem; Zidan, AM
The flow of a chemically reactive Burgers nanofluid with an induced magnetic field over an exponentially stretching surface is considered in this analysis. The thermal slip and concentration slip boundary conditions are considered to analyze the flow at the exponentially stretching surface in the current analysis. Furthermore, a heat transfer analysis is presented with the influence of heat generation/absorption and a variable thermal conductivity effect. Appropriate similarity variables are used to transfer the flow model into the coupled ordinary differential equations. These coupled equations are computed numerically by using the Boundary value problem (BVP) midrich technique. The impact of emerging parameters is examined graphically. It is found that the fluid velocity augments for the several values of relaxation parameters, while it shows the opposite trend for the retardation parameter. Further, it is found that the transfer rate of heat and mass boosted by increasing the values of relaxation and retardation parameters. A comparative investigation of the present article with the prevailing literature shows a remarkable agreement.